Curriculum coherence as perceived by district‐level stakeholders in large‐scale national curriculum reform in Finland. Issue 3 (3rd July 2019) - Sullanmaa, Jenni; Pyhältö, Kirsi; Pietarinen, Janne; Soini, Tiina
Abstract: It has been suggested that curriculum coherence is crucial in successful educational reform. However, empirical research on the topic is still scarce. This study explores how the stakeholders involved in curriculum development at the district level perceived curriculum coherence. Survey data ( n = 550) were analysed using structural equation modelling. A confirmatory factor analysis showed that curriculum coherence consists of three complementary components: consistency of the intended direction ; an integrative approach to teaching and learning ; and alignment between objectives, content and assessments . Moreover, the results showed that curriculum coherence contributes to the expected impact of the reform on the school level development. The study adds to the research on curriculum reform by showing that curriculum coherence is a central determinant of the reform taking root at the school level, and by introducing a scale for measuring perceptions of curriculum coherence within the context of large‐scale national curriculum reform.